Leadership for Educational Psychologists: Principles and Practicalities - Hardy, Julia; Bham, Mohammed; Hobbs, Charmian (BPS Textbooks in Psychology, 2020)
Written by and for educational psychologists, this valuable text includes reflections and practical support that will equip professionals to confidently handle the challenges inherent to leadership in the field for decades to come. The book: Meets a need to support new and existing educational psychologists (EPs) in understanding a range of leadership models Provides useful frameworks to apply to the Local Authority contexts where leaders are working Offers chapters that can be read independently as stand-alone topics or in sequential order Is derived from decades of courses for leaders of educational psychology Written by experienced educational psychologists (EPs) for other EPs in leadership positions and those aspiring to become leaders, this unique and practical book addresses a number of themes including the debate over the nature of leadership and the growing concern for equity and ethics in practice. It emphasises the importance of building and maintaining relationships at all levels, especially during challenging times. Leadership for Educational Psychologists: Principles & Practicalities offers chapters covering such topics as: managing educational psychology services (EPSs); past and present leadership frameworks; ethical leadership; change management;  women in leadership; inspirational and outward-facing leadership; educational psychology within a Welsh context; appreciative enquiry; recruitment and retention; managing data and quality standards; selling educational psychology services; and more. The book finishes with a section on available support mechanisms for EPs in leadership positions. Leadership for Educational Psychologists will be of great benefit to educational psychologists in leadership, including existing principal and senior educational psychologists, as well as those planning to move into promoted posts within EPSs. It will also be of interest to policymakers in local government, public sector leaders who manage professionals within local authorities, and voluntary and community organisations.